Monitoring of aquaculture in continental reservoirs using the trophic status index - Rosanova, Clauber; Pinho, Emilio Sousa; Matos, Flavia Tavares; Akama, Alberto; Bueno, Guilherme Wolf [UNESP]; Macedo, Daniela Barbosa (Univ Federal Mato Grosso, 2019)
Aquaculture is the fastest growing activity among food production sectors, however, its practice can cause environmental impacts, in case if a monitoring plan is not applied. The objective of the present study was to evaluate the trophic environment status using the Trophic State Index (TSI) in an aquaculture activity in a netcage system in the Lajeado reservoir, Palmas, Tocantins during the dry season. The monitoring was carried out from May / 2017 to August / 2017 and involved the water sampling for analysis of the following water quality parameters: total phosphorus and chlorophyll-a. At the same time, data were collected on temperature, turbidity, dissolved oxygen, conductivity, pH and total dissolved solids. The Trophic State Index (TSI) results showed that the area under study during the months of May and August was predominantly under a supereutrophic condition. It indicates that the lake trophic state in the aquaculture surrounding area is strongly influenced by external anthropogenic activities. Thus, the effects of this activity in the medium and long term are difficult to predict, so it's necessary to monitor and control the water quality.
Keywords: aquaculture; eutrophication; environmental impact; pollution; net cage